2014
DOI: 10.1111/1574-6941.12448
|View full text |Cite
|
Sign up to set email alerts
|

SymbioticChlorella variabilisincubated under constant dark conditions for 24 hours loses the ability to avoid digestion by host lysosomal enzymes in digestive vacuoles of host ciliateParamecium bursaria

Abstract: Endosymbiosis between symbiotic Chlorella and alga-free Paramecium bursaria cells can be induced by mixing them. To establish the endosymbiosis, algae must acquire temporary resistance to the host lysosomal enzymes in the digestive vacuoles (DVs). When symbiotic algae isolated from the alga-bearing paramecia are kept under a constant dark conditions for 24 h before mixing with the alga-free paramecia, almost all algae are digested in the host DVs. To examine the cause of algal acquisition to the host lysosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
(67 reference statements)
0
18
0
Order By: Relevance
“…Animals take advantage of mitochondria to generate energy to survive; energy is primarily generated from phagocytizing and digesting food particles through intracellular or extracellular digestion [22,23]. Previous studies have found that phagocytic intracellular digestion is the evolutionary cornerstone of digestive and immune mechanisms of multicellular animals [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Animals take advantage of mitochondria to generate energy to survive; energy is primarily generated from phagocytizing and digesting food particles through intracellular or extracellular digestion [22,23]. Previous studies have found that phagocytic intracellular digestion is the evolutionary cornerstone of digestive and immune mechanisms of multicellular animals [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Light availability is important for mixotrophs. For example, Chlorella symbionts provide photosynthetic products to their host under light conditions (Shibata et al, 2016), but they lost their ability to resist host digestion in darkness (Kodama and Fujishima, 2014). Heavy metals also affect protistan ingestion rates (Al-Rasheid and Sleigh, 1994) and physiology (Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that the increased number of acidic vacuoles of the symbiotic Chlorella spp. causes preferential digestion by the host lysosomal digestive enzymes during the early infection process ( Kodama and Fujishima, 2014 ). Kuchitsu et al (1987) showed that the algal vacuoles increase in number at the stationary phase compared with the algae in the log phase.…”
Section: Discussionmentioning
confidence: 99%